Academic perception on teaching approach of a multi-criteria decision making technique in the transportation engineering degree (Research, Society and Development, 2019)
This work aims at evaluating students’ perceptions about the Transportation Engineering degree at the Federal University of Mato Grosso, Várzea Grande Campus, as to a multicriterial decision technique used by a professors’ in two units of the respective course. Therefore, an online survey with 9 close-ended questions was elaborated. Subsequently, the survey has been sent to 23 students who have undertaken both the Economics and Operational Research units in Transportation, which were the units where the respective technique was approached. The questionnaire response rate was 56.52% since 13 students have answered the survey. The results have shown that the following procedures are considered as strong points: i) digital approach used by professors; ii) procedure adopted to solve students' doubts; and, iii) model exercise resolution in an online spreadsheet in practical classes. In addition, some of the strategies that can be adopted to improve students’ understanding of the AHP (Analytic Hierarchy Process) method are: i) providing students with material about the method beforehand and promoting its discussion, as well as ii) elaborating a guide for the assessed individual activities proposed by professors. Thus, it can be concluded that the way in which the multicriterial decision technique was approached was well evaluated according to the opinions of the students who studied two units.